An Architecture to Support Learning, Awareness, and Transparency in Social Software Engineering - Reinhardt, Wolfgang; Rinne, Sascha (International Journal of Emerging Technologies in Learning (iJET), 2010)
Classical tools for supporting software engineering teams (collaborative development environment, CDE) are designed to support one team during the development of a product. Often the required data sources or experts reside outside of the internal project team and thus not provided by these CDEs. This paper describes an approach for a community-embedded CDE (CCDE), which is capable of handling multiple projects of several organizations, providing inter-project knowledge sharing and developer awareness. The presented approach uses the mashup pattern to integrate multiple data sources in order to provide software teams with an exactingly development environment.